Fiscal Sustainability and Low Interest Rates: A Note - Martin Werding (Center for Economic Studies and Ifo Institute (CESifo), 2021)
In this paper, I demonstrate that an indicator which is commonly used to assess the long-term fiscal sustainability of public finances in EU member states (“S2”) is also defined if government borrowing rates are assumed to be permanently lower than the growth rate of GDP. I illustrate this finding based on simulations prepared for the Fifth Sustainability Report published by the German Federal Ministry of Finance. In addition, I discuss the interpretation of the indicator in a low-interest environment and the assumption that relevant interest rates continue to be low if there are substantial challenges for fiscal sustainability, e.g., through demographic ageing.
Keywords: H60; J11; E43; 330; public budget; public debt; fiscal sustainability; interest rates